Characterization of the bacterial midgut community of wild-caught Aedes aegypti - Shimizu, Julia, author; DuTeau, Nancy M., author (Colorado State University. Libraries, 2005)
It is estimated that 10 to the 14th power microbes make the human gut home, outnumbering the total number of cells in the body. The importance of microbes in the digestive system of mammals is fairly well known. However the microbial flora inhabiting the gut of insects, particularly mosquitoes, is less well studied. Understanding the microbial flora of the mosquito may provide valuable information for understanding why some mosquitoes are more effective vectors for human disease than others. Genetic alteration of these gut microbes may also lead to novel methods for controlling mosquito populations or blocking disease transmission. In this study, the microbial gut community of field-caught larval Aedes aegypti (the major vector of yellow fever and dengue) was analyzed. PCR products of bacterial 16S ribosomal RNA genes, amplified from larval DNA extracts, were cloned. 68 clones were then digested with Msp1. 57% of the clones had unique fragment patterns, while the other 43% shared one of 11 patterns, suggesting that the mosquito gut contains a diverse consortium of bacteria.
Characterization of the bacterial gut community in wild Aedes aegypti
Keywords: Aedes aegypti -- Physiology; Aedes aegypti -- Molecular aspects; Mosquitoes as carriers of disease